Associations Between Economic Pressure and Diabetes Efficacy in Couples with Type 2 Diabetes. Issue 2 (19th July 2017) - Novak, Joshua R.; Anderson, Jared R.; Johnson, Matthew D.; Walker, Ann; Wilcox, Allison; Lewis, Virginia L.; Robbins, David C.
Abstract : Objective: The purpose of this study was to explore dyadic associations between economic pressure and diabetes self‐efficacy via emotional distress in patients with type 2 diabetes and their partners. Background: Understanding how economic pressure is associated with successful diabetes management is an important area for research, as couples with type 2 diabetes can incur heavy economic pressures that could likely influence diabetes outcomes. Method: Data from 117 married couples were used to test actor–partner associations using moderated mediation analyses in a structural equation modeling framework. Problem‐solving communication was tested as a possible moderator of the economic pressure–emotional distress pathway. Results: Results revealed that greater patient economic pressure was associated with lower patient and spouse confidence in the patient's diabetes management ability through higher levels of patient emotional distress. The deleterious association between economic pressure and emotional distress was less pronounced when spouses reported more effective problem‐solving communication. Conclusion: These results provide evidence that the economic pressure couples with type 2 diabetes face may reduce the patient and spouse's confidence in the patient's diabetes management ability. Implications: This study demonstrates the importance of couple's relationship processes in buffering the impact of economic pressure on diabetes management, providing a clear target for intervention and education efforts.